All Days 2006
DOI: 10.2118/102469-ms
|View full text |Cite
|
Sign up to set email alerts
|

Acid Fracturing of Deep Gas Wells Using a Surfactant-Based Acid: Long-Term Effects on Gas Production Rate

Abstract: The deep, tight carbonate formations in Saudi Arabia are ideally suited for acid fracturing treatments. Various types of acids such as regular, in-situ gelled, and emulsified acids, have been used in order to achieve optimum fracture length and conductivity. Acids used for these treatments were based on 28 wt% HCl. A mixture of 15 wt% HCl and 9 wt% formic acid was used in wells completed with super Cr-13 tubulars. A high pH borate gel was pumped in stages to reduce leak-off and maintain the bottomhole pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…They found that increased acid-contact time sometimes reduced the fracture conductivity (weakening of the rock structure), whereas fluid loss can increase it, creating more surface roughness. They showed that the effect of rock-embedment strength and closure stress on acid-fracture conductivity is accurately predicted by the Nierode-Kruk correlation (Nierode and Kruk 1973).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that increased acid-contact time sometimes reduced the fracture conductivity (weakening of the rock structure), whereas fluid loss can increase it, creating more surface roughness. They showed that the effect of rock-embedment strength and closure stress on acid-fracture conductivity is accurately predicted by the Nierode-Kruk correlation (Nierode and Kruk 1973).…”
Section: Introductionmentioning
confidence: 99%
“…This model assumed an infinite reaction rate at the fracture surface, and the velocity and acid distributions were modeled after analytical solutions. Nierode and Kruk (1973) presented an evaluation of fluid-loss additives and retarded acids. They also presented correlations to predict fracture conductivity on the basis of the mass of the dissolved rock (ideal fracture width), assuming the walls dissolve uniformly.…”
Section: Introductionmentioning
confidence: 99%